Post-harvesting glyphosate and imazapyr application on Eucalyptus stumps to control coppice. Issue 3 (3rd July 2022) - Montes, W. G.; Tuffi Santos, L. D.; Barros, R. E.; de Paiva Ferreira, G. A.; Silva Donato, L. M.; Reis, M. M.; de Oliveira, L. S.
ABSTRACT: The objective of this research was to assess the efficiency of applying glyphosate and imazapyr to Eucalyptus cut-stump surfaces after harvesting to control sprouting. Two experiments were conducted in Eucalyptus grandis × Eucalyptus urophylla plantations arranged in a randomised block design with five treatments and five replicates. In experiment 1, 0, 0.84, 1.67, 2.50 and 3.34 kg of acid equivalent (a.e.) ha −1 of glyphosate was applied. Experiment 2 involved the application of 0, 0.028, 0.083, 0.140 and 0.195 kg a.e. ha −1 of imazapyr. The application was carried out between 42 and 48 hours after harvesting in replicates of 36 stumps. Increased glyphosate doses increased coppice control to more than 90%. Coppice was present on approximately 30% of the stumps treated with the highest glyphosate dose. However, these shoots showed low vigour 225 days after application, with mean values of about 0.30 m in height and 0.5 shoots per stump. In the control treatment, coppice reached 3.0 m in height and 8.0 kg green mass weight, and coppice was present on 97% of the stumps. The highest imazapyr doses increased shoot control to 80%. Post-harvesting application to cut stumps reduced coppice development. However, only the glyphosate doses of 2.50 and 3.34 kg a.e. ha −1 presented satisfactory coppice control levels without follow-up operations.